PENGEMBANGAN APLIKASI PRESENSI MAHASISWA SCAN QR CODE MENGGUNAKAN REACT NATIVE ANDROID STUDI KASUS POLITEKNIK PGRI BANTEN - Solihin, Solihin; Asrori, Khasan; Dodi, Dodi; Agustina, Dewi (Journal of Innovation And Future Technology (IFTECH), 2024)
This research aims to develop an Android-based student attendance application using React Native technology, with a case study at Politeknik PGRI Banten. Student attendance is crucial in academic activities as it serves as evidence of their presence and contributes to their overall academic assessment. However, the current attendance system at Politeknik PGRI Banten still relies on a website and does not provide a feature for students to view their attendance history. In this study, the author utilizes the JavaScript programming language with the React Native framework to develop an Android-based attendance application. The application leverages QR code scanning technology to optimize the student attendance process. Students can scan the QR code on their student identification cards using their mobile phone camera, and the attendance data will be recorded directly in the database. The development of this attendance application is expected to enhance the technological quality of Politeknik PGRI Banten, in line with the society 5.0 era that requires the utilization of information system technology to improve efficiency and enhance human life quality. Moreover, the application provides convenience for students to access and view their attendance history in each course, which was previously unavailable in the existing attendance system.